2009
DOI: 10.1016/j.febslet.2009.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Adding structural information to the von Hippel–Lindau (VHL) tumor suppressor interaction network

Abstract: a b s t r a c tThe von Hippel-Lindau (VHL) tumor suppressor gene is a protein interaction hub, controlling numerous genes implicated in tumor progression. Here we focus on structural aspects of protein interactions for a list of 35 experimentally verified protein VHL (pVHL) interactors. Using structural information and computational analysis we have located three distinct interaction interfaces (A, B, and C). Interface B is the most versatile, recognizing a refined linear motif present in 17 otherwise non-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 63 publications
(77 reference statements)
1
37
0
Order By: Relevance
“…We found that both GST-pVHL 1–173 and GST-pVHL 1–114 were able to bind p45 AUF1 , indicating that deletion of the Elongin C-binding pVHL α domain did not affect AUF1 binding (Figure 4B). We also tested GST-pVHL β domain mutations that correspond to truncation at each of the first 4 β sheets as indicated in Figure 4B (3, 4). Deletion of β sheet 4 (construct 1–101) and β sheet 3 (construct 1–89) did not disrupt p45 AUF1 binding, while p45 AUF1 binding to the GST-pVHL 1–78 construct was diminished (Figure 4B), suggesting that AUF1 requires either β sheet 2, the loop between β sheet 1 and 2, or both for binding to pVHL.…”
Section: Resultsmentioning
confidence: 99%
“…We found that both GST-pVHL 1–173 and GST-pVHL 1–114 were able to bind p45 AUF1 , indicating that deletion of the Elongin C-binding pVHL α domain did not affect AUF1 binding (Figure 4B). We also tested GST-pVHL β domain mutations that correspond to truncation at each of the first 4 β sheets as indicated in Figure 4B (3, 4). Deletion of β sheet 4 (construct 1–101) and β sheet 3 (construct 1–89) did not disrupt p45 AUF1 binding, while p45 AUF1 binding to the GST-pVHL 1–78 construct was diminished (Figure 4B), suggesting that AUF1 requires either β sheet 2, the loop between β sheet 1 and 2, or both for binding to pVHL.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, interaction with the CDKN1 protein family may have evolved to allow transmission of a generic hypoxic signal to other signaling pathways, re-using the same pVHL adaptor protein. Intriguingly, the same pVHL region5354 mediates its association with over 40 proteins beyond HIF-1/2α54, implying multiple factors in dynamic competition to alternatively associate unbound pVHL in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The binding domains of HIF1/2α (amino acid 67-117), p53 (aa 154-163) and Elongin C (aa 157-171) were assessed as described by Leonardi et al [49]. We selected four mutations that were located in the overlap of p53 and EloC binding domains of pVHL (aa 157-163): three were predicted to have no or little impact on the protein stability (Leu158Val, Arg161Gln, Cys162Arg, mild impact) and one was predicted to highly destabilize pVHL (Arg161Pro, high impact).…”
Section: Methodsmentioning
confidence: 99%